Hymes’ SPEAKING Factors Analysis in La La Land film by Damien Chazelle: Ethnographical Study - Darnawati Darnawati; Dodi Oktariza; Vera Magria (Krinok:Jurnal Linguistik Budaya, 2019)
This thesis is analyzes about SPEAKING in film La La Land. the purpose of this research is to explain SPEAKING factors that happen in the film. This research uses descriptive qualitative method because the data are in the forms of utterances.This research is done by some steps, they are data collecting, data analyzing and data presentation. In technique of collecting the data, the writer uses the non participant observational method. The implementation of this method is realized through downloading and note technique. In technique of analyzing the data, the writer uses identity method and referential identity method. The data are presented through informal method.The result of the research by using ethnography of communication  as an approach in  La La Land film shows some which are includes complaining, ordering, confiding, getting fired, agreement, casting audition, disappointment, and argument. Each of these situation, in turn were affected by SPEAKING factors as Hymes suggested which are the  setting, the participants, their ends, the instrument, the norms  and the genre of the communication. The writer takes 11 data from the film. the writer concludes that La La Land film shows some situation which are includes complaining and ordering that are common to be happen in a shop as seen in the film. Key words : SPEAKING Factors, La La Land,  Ethnography of  Communication